Pathophysiology, Diagnosis, and Treatment of Radiation Necrosis in the Brain - YORITSUNE, Erina; NONOGUCHI, Noasuke; FURUSE, Motomasa; KUROIWA, Toshihiko; MIYATA, Tomo; MIYATAKE, Shin-Ichi; KAWABATA, Shinji (Neurologia medico-chirurgica, 2015)
New radiation modalities have made it possible to prolong the survival of individuals with malignant brain tumors, but symptomatic radiation necrosis becomes a serious problem that can negatively affect a patient’s quality of life through severe and lifelong effects. Here we review the relevant literature and introduce our original concept of the pathophysiology of brain radiation necrosis following the treatment of brain, head, and neck tumors. Regarding the pathophysiology of radiation necrosis, we introduce two major hypotheses: glial cell damage or vascular damage. For the differential diagnosis of radiation necrosis and tumor recurrence, we focus on the role of positron emission tomography. Finally, in accord with our hypothesis regarding the pathophysiology, we describe the promising effects of the anti-vascular endothelial growth factor antibody bevacizumab on symptomatic radiation necrosis in the brain.